(untitled) (PerCursos, 2025)
This essay focuses on the uses of technologies in the territory of paraskateboard, analyzing the television documentary "Skateboard Changed My Life", produced in 2024 and broadcast by Canal Off and Globoplay. Organized in 10 episodes that present the stories of Brazilian paraskaters, the audiovisual material raised questions about technological incrporation in this modality. The main of this article was to reflect on the ways in which the paraskateboarders portrayed in the aforementioned series use the tools – prosthetics, crutches, and the skateboard itself – that shape and enhance their sposrts performances, considering the distinct corporealities marked, among other things, by disabilities. From the analysis of the media material, concerns emerged about the necessary adjustments for paraskateboard to reach the Paralympic competitions; how these bodies with disabilities (essentially physical and blindness/low vision) perform on the four-wheeled board; and how skateboard is established as a technological apparatus alongside prostheses (often refuted) and canes.